(untitled) (Acta Scientiarum. Health Sciences, 2013)
Acute respiratory infections are frequent and are the leading cause of infant morbidity and mortality. This study aimed to verify the socioeconomic profile of children hospitalized with community-acquired pneumonia. We realized a prospective study where social data were collected by direct interview conducted with parents and guardians and supplemented by information from medical records of children under five years of age hospitalized in wards at Hospital Infantil Pequeno Príncipe in the city of Curitiba. All children had clinical and radiological diagnosis of pneumonia. Twenty-two children were included in the study so. Eighteen children (82%) had family incomes below three minimum wages. In 36% (n = 8) of cases the mother worked outside the home. Living with household smokers was also observed in 36% of cases. Elementary education was found in 82% of mothers. Seventeen children (77%) were breastfed for less than six months. Nine children attended day care. Less than 14% (n = 3) of the children were daughters of teenage mothers. This study underscored the importance of socioeconomic factors on the morbidity of community pneumonia in childhood, being family income, maternal education and early weaning the factors most frequently rated among the internees.